Understanding the Primacy of Geography in the Conduct of Foreign Policy - Bhattarai, Dinesh (Journal of Foreign Affairs, 2022)
Geopolitics has returned to reassert and manifest itself in various ways. The management of the geopolitics has emerged as the central challenge of the day. The rise of China and emergence of India as great economic powers containing 40 percent of the world’s population, and a huge market is one of the most important geopolitical developments of contemporary human history. This has caused monumental shift with a few parallels in the world history. While exposing the vulnerabilities of the world, Covid19 and climate change have accelerated these trends. The advent of globalization intensified the process of massive social awakening, radicalizing the politics. Market forces would determine the free flow of goods, services, capital, and technology. The latest developments indicate geopolitical considerations driving trade policy and economic integration to reflect geographic, cultural, and strategic direction. The hard lessons from emerging geopolitics include the ongoing rivalry between the US and China, newly assertive Russia and its invasion of Ukraine, Sino- Indian border clashes pushing for deeper US-India partnership. The elevation of the Indo-Pacific as the center piece of US regional strategy has raised the contours of competition and rivalry in the region. Nepal’s geographical location between India and China has gained greater prominence and higher sensitivity in the changed context with the geopolitical challenges and economic dynamism of its neighbours at its doorsteps, Nepal’s friendship with both of these neighbors’ and United States remains of paramount importance in the conduct of its foreign policy. A stable, democratic, and prosperous Nepal stands as the anchor of regional stability and security. Upon the same realization, this qualitative study is an attempt to explain how the primacy of geopolitics has come back and how it is being played.